Prevalence of hypertension and its risk factors among individuals attending outpatient department of rural health training centre, Haldwani - Bartwal, Janki; Awasthi, Sadhana; Rawat, Chandra Mohan Singh; Singh, Rajesh Kumar (Indian Journal of Community Health, 2014)
Introduction: Hypertension is one of the major health and development challenges of the 21st century, which, for most countries, has developed together with rapid cultural and social changes, ageing populations, increasing urbanization, dietary changes, reduced physical activity, and other unhealthy behaviours. Objectives: 1) To find out the prevalence of Hypertension in study subjects 2) To identify the risk factors associated with Hypertension. Materials and Methods: A Cross-sectional study was carried out among 369 individuals of 30 years and above attending Out Patient Department (OPD) in Rural Health Training Centre (RHTC) under the Department of Community Medicine, Government Medical College, Haldwani during June 2013-August 2013. A pretested predesigned questionnaire was used to collect demographic data by interview technique .The blood pressure was recorded and classified using JNC VII criteria to grade hypertension. Data was compiled, entered & analyzed using SPSS version 20. Results: Among 369 patients, the prevalence of hypertension was 41.7%; out of this, 28.7% were aware of their hypertensive status while 13% were newly diagnosed cases. The association between hypertension with increase in age, family history of hypertension, increase salt intake, consuming mixed diet, increase waist circumference, waist hip ratio and body mass index was found significant. Physical inactivity, gender, tobacco and alcohol consumption were not significantly associated with hypertension. Conclusions: The prevalence of hypertension in rural area is relatively high. Extensive efforts are required for raising the awareness level & regular screening of high-risk population is recommended for preventing the complications & disability.